Centenarul la polonezi și la români. Istoria unei retorici culturale (Romanian Studies Today, 2024)
Starting from the centenary of the Great Union and, respectively, of the Regainment of Independence, celebrated by Romanians and Poles in 2018, the text confronts the contemporary perspective on them with the historical realities from one hundred years ago. The author declares himself against the thesis according to which there are similarities between the historical fate of the two states/nations and he proves this through a series of arguments. It is analyzed, among others, the internal political situation in both of the countries, the position of the interwar political leaders (Piłsudski, Dmowski, Averescu, Brătianu etc.), the  confrontations of ideas etc. A special chapter is dedicated to the way of perceving of the historical moment of 1918 during the communist period.
Keywords: the Great Union; the Regainment of Independence; nationalism; social conflict; interwar period